Surface plasmon polariton modes in coaxial metal-dielectric-metal waveguides - Marie Anne van de Haar; Ruben Maas; Benjamin Brenny; Albert Polman (New Journal of Physics, 2016)
We explore the optical properties of a coaxial plasmonic metamaterial consisting of hollow dielectric cylinders with a diameter of 100–250 nm and a ring wall width of 10–50 nm, embedded in metal. We investigate the modal electric and magnetic fields and dispersion relation for different geometries and material choices of a single coaxial channel by using realistic values for all design parameters. The Fabry–Pérot modes of a finite thickness slab are investigated with cathodoluminescence spectroscopy and explained by extracting the mode index from FDTD simulations. Furthermore, we investigate the coupling behavior of adjacent coaxes inside a hexagonal array. We find a change from the single-ring dispersion relation for coaxes with a ring-to-ring distance smaller than 20 nm.